Alternative therapeutics to control antimicrobial resistance: a general perspective - Singha, Biplab; Singh, Vinayak; Soni, Vijay (Frontiers in Drug Discovery, 2024)
Antimicrobial Resistance (AMR) is a critical global health challenge, and in this review article, we examine the limitations of traditional therapeutic methods and the emerging role of alternative therapies. By examining the reasons behind the failure of conventional treatments, including the inadequacy of one-drug-one-enzyme approaches, the complex evolution of AMR, and the impact of drug biotransformation, we better understand why conventional treatments failed. Moreover, the review discusses several alternative therapies, including RNA-based treatments, aptamers, peptide-based therapies, phage therapy, and probiotics, discussing their applications, advantages, and limitations. Additionally, we discuss the obstacles to develop these therapies, including funding shortages, regulatory barriers, and public perception. This comprehensive analysis aims to provide insight into the future of AMR, emphasizing the need for innovative strategies and practical approaches.